Role of ligamentum flavum in the symptomatology of prolapsed lumbar intervertebral discs. - Ramani, P S (1975)
Hypertrophy of the ligamentum flavum has been reported to occur in the prolapsed intervertebral disc syndrome. The ligaments from 28 patients were compared with a necropsy control group (18). Only minor histological anomalies were noted in two patients and the ligament was not thickened in cases of disc prolapse. In addition, there was no evidence to suggest previous trauma to the ligaments associated with disc protrusion or that the elastic fibres in the ligament degenerate with age, although some degeneration of the collagen fibres had apparently occurred in the two oldest control cases.